Contemporary Methods for Quantifying Submarine Groundwater Discharge to Coastal Areas - Ray, Ram L.; Dogan, Ahmet (SPRINGER INTERNATIONAL PUBLISHING AG, 2016)
Submarine Groundwater Discharge (SGD), which represents subsurface exchange of water between land and ocean, is a major component of the hydrological cycle. Until the mid-1990s, it was generally believed that SGD rates were not large enough to influence ocean water budgets. This thought might be due to the difficulty in quantifying rates of SGD, because most SGD occurs as diffusive flow, rather than discrete spring flow. However, there is a growing recognition that the submarine discharge of fresh groundwater into coastal oceans is just as important as river discharge in some areas of the coastal ocean. Due to growing ecological concerns about SGD, there is considerable progress on research about SGD with particular emphasis on how to quantify and trace the SGD, and to develop some forecasting or predictive capability of SGD rates based on climatic and seasonal effects. This chapter presents a comprehensive overview of the methods used to quantify SGD to coastal areas and summarizes the previous studies on SGD. In addition, this chapter also discusses driving forces of groundwater flow through coastal aquifers, mechanism of groundwater seawater interaction and some other important issues that are necessary to understand the methods for quantifying SGD in coastal areas. The main goal of this chapter is to provide an overview of the applied methodologies to quantify SGD in coastal areas, which in turn will allow researchers, coastal zone managers, and others to choose appropriate methods that meet their specific project requirements.
Keywords: WATER DISCHARGE; SEEPAGE; BAY; VARIABILITY; INTRUSION; NUTRIENTS; FLOW; SEA; CONSEQUENCES; SIMULATION; Water Resources